She loved baseball : the Effa Manley story - Vernick, Audrey (HarperCollins, 2010)
Effa always loved baseball. As a young woman, she would go to Yankee Stadium just to see Babe Ruth's mighty swing. She never dreamed she would someday own a baseball team, or be the first and only woman ever inducted into the Baseball Hall of Fame. From her childhood in Philadelphia to her groundbreaking role as business manager and owner of the Newark Eagles, Effa Manley always fought for what was right. And she always swung for the fences.